2017
DOI: 10.5604/12321966.1232759
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in long-term survivors of early stage endometrial cancer

Abstract: Introduction. Endometrial cancer (EC) is the most common gynaecological malignancy in developed countries. Effective treatment of the early stage of the disease is achieved by surgery alone. An increasing number of patients with EC become long-term survivors; therefore, the purpose of this study was to investigate the quality-of-life (QOL) of EC survivors. Materials and Method. A total of 328 survivors who had completed cancer treatment more than 3 years ago, and had previously completed questionnaires concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…Many of the studies that have examined long-term outcomes among endometrial cancer survivors had small sample sizes, lacked a comparison group, or relied on patient-reported outcomes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Studies that examine risk for long-term cardiovascular outcomes among endometrial cancer survivors are becoming increasingly more critical because of the high overall survival rate among individuals diagnosed with endometrial cancer, the large number of endometrial cancer survivors, the projected increase in the number of endometrial cancer diagnoses (3), the introduction of more complex therapies, and the high mortality due to cardiovascular disease among endometrial cancer survivors.…”
mentioning
confidence: 99%
“…Many of the studies that have examined long-term outcomes among endometrial cancer survivors had small sample sizes, lacked a comparison group, or relied on patient-reported outcomes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Studies that examine risk for long-term cardiovascular outcomes among endometrial cancer survivors are becoming increasingly more critical because of the high overall survival rate among individuals diagnosed with endometrial cancer, the large number of endometrial cancer survivors, the projected increase in the number of endometrial cancer diagnoses (3), the introduction of more complex therapies, and the high mortality due to cardiovascular disease among endometrial cancer survivors.…”
mentioning
confidence: 99%
“…A previous Thai work by Prasongvej and colleague reported that cervical cancer survivors had better functional QoL than other women with similar characteristics (Prasongvej et al, 2017). However, reports from Poland, Germany and the Netherland yielded similar symptom scales when compared endometrial cancer survivors and those with no cancer (Dobrzycka et al, 2017;Becker et al, 2011;de Boer et al, 2015). Different types of cancer seem to impact patient symptom scales differently.…”
Section: Symptom Scalesmentioning
confidence: 89%
“…Literature from Poland, Germany, the Netherland, and Italy reported that there was no significant global health status QoL difference between endometrial cancer survivors and their control groups (Dobrzycka et al, 2017;Becker et al, 2011;de Boer et al, 2015;Ferrandine et al, 2014). Chinese and Turkish works reported lower global health status among gynecologic cancer survivors who received wider area of radiation treatment.…”
Section: Global Health Statusmentioning
confidence: 99%
See 2 more Smart Citations